Terapi Psikoreligius Dalam Pengendalian Emosi Pada Lansia Di Panti Tresna Werdha Palembang - Sely Fitriani; Suryati suryati; Neni Noviza (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This research is entitled "Psychoreligious Therapy in Controlling the Emotions of the Elderly at the Tresna Werdha Social Home in Palembang". Low emotional control will give rise to various negative attitudes and is not good for the physical and psychological health of the elderly themselves. Psychoreligious therapy is needed which is expected to be able to control the emotions of the elderly. Psychoreligious therapy as a treatment in the practice of caring for the soul using a religious approach. This research aims to determine the emotional description of the elderly and find out Psychoreligious Therapy in Controlling the Emotions of the Elderly at the Tresna Werdha Social Home in Palembang. This research uses a qualitative approach with field study methods. The subjects of this research were four people consisting of two elderly people, namely the client "NA" and client "S" and social home employees namely "M" and "P". Data collection techniques used were observation, interviews and documentation. Data analysis techniques were data condensation, data presentation and conclusions, withdrawal/verification. The results of the research show that the description of emotional control in the elderly or "NA" clients, and "S" clients experience difficulties in establishing new relationships with other people or other elderly people who are in the orphanage. Application of psychoreligious therapy in controlling the emotions of the elderly in the Tresna Werda social institution Palembang which consists of three stages, namely takhalli (intended to empty or cleanse the heart of bad qualities that can cause emotions), tahalli (an effort to adorn oneself with commendable morals, by being physically and mentally obedient) and Tajalli (the final result obtained by a person after he succeeded in training himself and restraining himself seriously so that he achieved true calm and happiness in the form of a complete disappearance of emotions, pain and troubles in life.